2021
DOI: 10.1177/1550059421991685
|View full text |Cite
|
Sign up to set email alerts
|

Differences of EEG Frequency and Spatial Parameters in Depressive Female Adolescents With Suicidal Attempts and Non-suicidal Self-injuries

Abstract: Background. Both non-suicidal self-injuries (NSSIs) and suicidal attempts (SAs) in adolescence represent significant risk factors for consequent suicide, but neurophysiological markers and predictors of these two forms of auto-aggressive behavior have been studied insufficiently. Objective. The aim of the study was to identify the differences of electroencephalographic (EEG) frequency and spatial parameters between depressive female adolescents with solely NSSI, and with combined NSSI + SA behavior in their hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…This further supported a distinction between people with NSSI, SI, SA, or co-occurrence of STBs. While previous studies already found a distinction between people with SA only and both NSSI + SI in terms of brain functioning (Iznak et al, 2021), cognitive styles (Wolff et al, 2013), and psychiatric prognosis (Bjureberg et al, 2022), our results further indicated a difference between the developmental risks and potential mechanisms underlying all these complex profiles of STBs.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This further supported a distinction between people with NSSI, SI, SA, or co-occurrence of STBs. While previous studies already found a distinction between people with SA only and both NSSI + SI in terms of brain functioning (Iznak et al, 2021), cognitive styles (Wolff et al, 2013), and psychiatric prognosis (Bjureberg et al, 2022), our results further indicated a difference between the developmental risks and potential mechanisms underlying all these complex profiles of STBs.…”
Section: Discussioncontrasting
confidence: 72%
“…Moreover, Victor and Klonsky (2014) found that adolescents with higher frequency and numbers of NSSI methods also show more violent manners of SAs in adolescents, indicating the importance of identifying risk factors predicting both individual STBs and the co-occurrence of multiple STBs. In line with this, several studies have found differences between people with SA and people with NSSI + SA in brain functioning (Iznak et al, 2021), cognitive styles (Wolff et al, 2013), and psychiatric prognosis (Bjureberg et al, 2022). This indicated more complex dynamic interactions between single STBs and the co-occurrence of STBs.…”
mentioning
confidence: 60%
“…The reason false alarms exist is that the data collected could not give a full view of high-suicide-risk students. False alarms remind us to include more aim indicators in data collection, such as impulsivity, near-infrared spectroscopy (NIRS), electroencephalogram (EEG), and some genetic indices ( Lutz et al, 2017 ; Hirose et al, 2018 ; Costanza et al, 2021 ; Iznak et al, 2021 ; Koenig et al, 2021 ). Lifetime SA was significantly associated with both higher impulsivity and higher aggression ( Costanza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For alpha, the activity appears to begin approximately 500 ms post-feedback. Given previous work (Iznak et al, 2021) and current findings, alpha activation was evaluated at POZ. The alpha PCA accounted for 64.89% of the variance.…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…Even fewer studies have examined high-frequency (HF) measures, such as alpha, beta-1, beta-2, and gamma related to suicide and/or feedback processing. One study measured an increase in alpha spectral power in the parieto-occipital area for those with suicidal attempts compared to those with non-suicidal self-injuries (Iznak et al, 2021). In another, non-suicidal depressed patients displayed decreased beta and low gamma activity in the frontal regions (Benschop et al, 2019).…”
Section: Introductionmentioning
confidence: 99%